2012
DOI: 10.1074/jbc.m112.340794
|View full text |Cite
|
Sign up to set email alerts
|

Cross-seeding and Conformational Selection between Three- and Four-repeat Human Tau Proteins

Abstract: Background: K18/K19 Tau protein isoforms can aggregate into different amyloid-β-like fibrils.Results: Different K18/K19 oligomers can be templates for fibril growth via cross-seeding between K18 and K19.Conclusion: K18 and K19 octamers create different cross-seeding barriers promoting K18 growth on K19 seeds but preventing K19 growth on K18.Significance: Conformational selection of compatible states during cross-seeding of amyloid species is general in amyloid-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 41 publications
8
70
0
Order By: Relevance
“…This is similar to the salt bridge distributions in K18 and K19 fibrils. 33 As shown in Supporting Information Figure S6a and b, the binding of tau protein to Aβ oligomer increases tau K18 and K19 residues exposed hydrophobic surface area, particularly the two nucleating segments ( 275 VQIINK 280 ) in R2 and ( 306 VQIVYK 311 ) in R3. Exposure of such mainly hydrophobic segments would facilitate the association of tau with these hydrophobic segments of a second tau monomer through hydrophobic interactions, leading to tau aggregation and nucleation.…”
Section: Lettermentioning
confidence: 88%
See 1 more Smart Citation
“…This is similar to the salt bridge distributions in K18 and K19 fibrils. 33 As shown in Supporting Information Figure S6a and b, the binding of tau protein to Aβ oligomer increases tau K18 and K19 residues exposed hydrophobic surface area, particularly the two nucleating segments ( 275 VQIINK 280 ) in R2 and ( 306 VQIVYK 311 ) in R3. Exposure of such mainly hydrophobic segments would facilitate the association of tau with these hydrophobic segments of a second tau monomer through hydrophobic interactions, leading to tau aggregation and nucleation.…”
Section: Lettermentioning
confidence: 88%
“…These observations are consistent with previous studies of crossseeding between K18 and K19. 32,33 R2 is the dominant K18 repeat. Because it is missing in K19, K18 cannot seed K19.…”
mentioning
confidence: 99%
“…Both amyloid seeds from hIAPP and Aβ peptides could serve as the interacting precursors to mutually promote the amyloid elongation. Consistently, a number of studies have reported that amyloids from different species or with different sequences can overcome cross-seeding barriers to form cross-seeding aggregates and fibrils via the elongation pathway if they have close structural similarity, including tau-k18 and tau-k19 [84][85][86][87] , Aβ and tau 29 , and hIAPP and rIAPP 25 . Meanwhile, it is interesting to note that the tail-tail model also had a relatively higher population of 21.1%.…”
Section: Structural Populations Of Polymorphic Aβ-hiapp Assembliesmentioning
confidence: 79%
“…The PHFs can get through the adjacent cells, then induce fibrillization of intracellular human Tau in these naive recipient cells via direct protein-protein contact [43,44]. The filaments can form not only by the full-length human Tau protein, but also by the three repeated or four repeated Tau segments, and there is cross-seeding and conformational selection between both Tau segments [45]. Following a similar paradigm, intracerebral injection of mutant Tau aggregate-containing brain extracts can cause widespread aggregation of normal human Tau in transgenic mice that do not otherwise develop aggregates [46,47], and aggregated Tau can initiate neurofibrillary tangle formation in vivo [48].…”
Section: Prion-like Protein Aggregation: Tau Protein Aggregationmentioning
confidence: 99%